2021
DOI: 10.5252/cryptogamie-mycologie2021v42a1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lichen Secondary Chemistry Doubled the Number of Cetrelia W.L. Culb. & C.F. Culb. Species (Parmeliaceae, Lichenised Ascomycota) in Hungary

Abstract: The distribution patterns of lichen secondary metabolites are often taxon specific. They represent cryptic chemical diversity additional to morphological-anatomical biodiversity. Cetrelia W.L. Culb. & C.F. Culb. species (c. 200 specimens) were checked and revised by thin-layer chromatography. Soredia, pseudocyphellae, rhizines, features of lower surface are the main morphological characters analysed against the presence of cortical pigment, atranorin and medullary α-alectoronic acid, anziaic acid, α-collatolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The subpopulations of Cetrelia species in eastern North America have contrasting frequency and distrubtion patterns relative to their disjunct European subpopulations. Notably, C. chicitae is common and widespread in eastern North America whereas in Europe it is extremely rare, and found mainly by targeted efforts (Farkas et al 2021; Kukwa & Motiejūnaitėe 2010; Obermayer & Mayrhofer 2007). Likewise, C. monachorum is restricted to high elevation sites in eastern North Amerrica, but typically cooccurs with C. chicitae in equal or less abundance (Howland & Lendemer, pers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subpopulations of Cetrelia species in eastern North America have contrasting frequency and distrubtion patterns relative to their disjunct European subpopulations. Notably, C. chicitae is common and widespread in eastern North America whereas in Europe it is extremely rare, and found mainly by targeted efforts (Farkas et al 2021; Kukwa & Motiejūnaitėe 2010; Obermayer & Mayrhofer 2007). Likewise, C. monachorum is restricted to high elevation sites in eastern North Amerrica, but typically cooccurs with C. chicitae in equal or less abundance (Howland & Lendemer, pers.…”
Section: Resultsmentioning
confidence: 99%
“…The subpopulations of Cetrelia species in eastern North America have contrasting frequency and distrubtion patterns relative to their disjunct European subpopulations. Notably, C. chicitae is common and widespread in eastern North America whereas in Europe it is extremely rare, and found mainly by targeted efforts (Farkas et al 2021; Habitat quality assessment. Quantifying the frequency of Cetrelia occurrence compared to habitat quality revealed that all species had a strong affinity to high quality habitats (Fig.…”
Section: Geographic Distribution In Eastern Northmentioning
confidence: 99%
“…For the genus Cetrelia, an assessment of the composition of secondary metabolites allowed for a confirmation of the presence of species only reported in America in Europe, as in the case of C. chicitae. Metabolite composition has also facilitated the confirmation of new species for the genus by chemical fingerprinting, which contrasts the phenotypic plasticity of some morphological characters used for identification [54]. In the genus Psoroma, an analysis of the distribution of secondary metabolites has validated the presence of chemical markers unique to the group, and the presumed description of subgenera by taxa heterogeneity, causing spatial segregation [55].…”
Section: Distance and Phylogenetic Analysismentioning
confidence: 99%
“…HPTLC was also applied in addition to morphological investigations during identifications and revisions of Hungarian herbarium material (Farkas et al . 1998, 2021).…”
Section: Introductionmentioning
confidence: 99%